Quorum sensing: cell-to-cell communication in Saccharomyces cerevisiae - Li, Linbo; Pan, Yuru; Zhang, Shishuang; Yang, Tianyou; Li, Zhigang; Wang, Baoshi; Sun, Haiyan; Zhang, Mingxia; Li, Xu (Frontiers in Microbiology, 2023)
Quorum sensing (QS) is one of the most well-studied cell-to-cell communication mechanisms in microorganisms. This intercellular communication process in Saccharomyces cerevisiae began to attract more and more attention for researchers since 2006, and phenylethanol, tryptophol, and tyrosol have been proven to be the main quorum sensing molecules (QSMs) of S. cerevisiae. In this paper, the research history and hotspots of QS in S. cerevisiae are reviewed, in particular, the QS system of S. cerevisiae is introduced from the aspects of regulation mechanism of QSMs synthesis, influencing factors of QSMs production, and response mechanism of QSMs. In this paper, the research history and hotspots of S.cerevisiae, and the progress of research methods of yeast QS, including cell morphology, QSM monitoring, gene knockout, and omics studies related to QS are reviewed. In particular, the QS system of S. cerevisiae is introduced through the following aspects, synthesis of QSMs, influencing factors of QSMs production, and response mechanism of QSMs. Finally, the employment of QS in adaptation to stress, fermentation products increasing, and food preservation in S. cerevisiae was reviewed. This review will be useful for investigating the microbial interactions of S. cerevisiae, will be helpful for the fermentation process in which yeast participates, and will provide an important reference for future research on S. cerevisiae QS.